2015
DOI: 10.1186/s13054-015-0913-x
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol attenuates hemorrhage and accelerates wound healing in severely burned adults

Abstract: IntroductionPropranolol, a nonselective β-blocker, exerts an indirect effect on the vasculature by leaving α-adrenergic receptors unopposed, resulting in peripheral vasoconstriction. We have previously shown that propranolol diminishes peripheral blood following burn injury by increasing vascular resistance. The purpose of this study was to investigate whether wound healing and perioperative hemodynamics are affected by propranolol administration in severely burned adults.MethodsSixty-nine adult patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 29 publications
(29 reference statements)
4
68
0
Order By: Relevance
“…The latter may be positively influenced due to the additional angionetic effects of β-blockers [25]. Most of these effects were detected after oral or systemic application, respectively [9, 10]. In serum equivalent applications they see­med to have less influence on keratinocytes and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The latter may be positively influenced due to the additional angionetic effects of β-blockers [25]. Most of these effects were detected after oral or systemic application, respectively [9, 10]. In serum equivalent applications they see­med to have less influence on keratinocytes and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…HPC have been found within healing lungs as well as skin (34, 35). In addition, beta adrenergic receptors are found widely in fibroblasts, keratinocytes, endothelial cells, as well as HPC (3638). In particular, the mobilization of HPC was shown to be mediated through beta 2 and 3 adrenergic receptors (38, 39).…”
Section: Discussionmentioning
confidence: 99%
“…Further study demonstrating the importance of propranolol dosing in wound healing was done by Zhang et al (42) who demonstrated that propranolol infusion at 1 mg/kg/hr in rabbits (significantly less than the 50 mg/kg doses in rabbits) did not negatively impact wound reepithelialization. Clinically most relevant, in adult burn patients that received an average of 3 mg/kg/day of propranolol there was an associated improvement in donor site healing time (36). …”
Section: Discussionmentioning
confidence: 99%
“…(93, 94) There have been several studies in burn patients demonstrating that propranolol improves wound healing, decreases cardiac work, and reduces metabolic demands without causing significant arterial hypotension or metabolic dysregulation. (9597) Rodent models have provided the pathophysiologic basis for these clinical advances. Stress response pathways, including p38 MAPK, JNK, and NF-κB, are activated by scald burn injury and have been effectively blocked with propranolol.…”
Section: Burns and Wound Healingmentioning
confidence: 99%